Gorham's Disease of the Maxilla and Mandible With Distinctive Cone Beam Computerized Tomographic Features - Rupam Sinha; Soumyabrata Sarkar; Tanya Khaitan; Deepsikha Ramani (Iranian Society of Pathology, 2017)
Gorham's disease is a rare and atypical disorder epitomized by progressive osteolysis of bone with eventual total disappearance of bone. The etiology is poorly understood with variable clinical presentation. Most times it is initially misdiagnosed as temporomandibular joint dysfunction, periodontal disease or odontogenic tumors clinically and radiographically in routine dental practice. Radiographic examination, such as Cone Beam Computerized Tomography (CBCT) play a vital role in diagnosing such disorder resulting in disappearance of the involved bone entirely, which is a definitive distinguishing feature of this condition. Regarding the rarity of the condition, the current study presents a case of Gorham's disease with distinctive clinical, radiological, and histological, features involving maxilla and mandible.